2020
DOI: 10.1080/14724049.2020.1751650
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the scope of resources in nature: an explorative study of nature-based tourism firms

Abstract: Nature-based tourism firms and other stakeholders often compete for the same resources. Knowledge of and access to resource bases are therefore essential for firms' success. Nature-based tourism firms operate in nature areas, which, for the Nordics, may include human-made objects and intangibles. In this study, we therefore adopt a broad approach towards the concept of natural resources and include human-made, social, and cultural resources, termed resources in nature. Based on 558 survey responses, we analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This positively influence the income of the people too. This result is supported the study that found the commercial value of the resources as inputs to the tourism production process increases when recreational activities are organized and charged for [27].…”
Section: The Economy Subsystemsupporting
confidence: 81%
“…This positively influence the income of the people too. This result is supported the study that found the commercial value of the resources as inputs to the tourism production process increases when recreational activities are organized and charged for [27].…”
Section: The Economy Subsystemsupporting
confidence: 81%
“…The sustainable use of natural capital can be achieved, for example, by implementing NbT activities linked to certain productive activities such as livestock and agroforestry. Along with better management of nature, these initiatives can contribute to reducing poverty by diversifying community activities and enhancing their adaptive capacities (Fossgard and Stensland 2021;Samora-Arvela et al 2020). Diversification is important because many households in rural or semi-urban communities rely on only one or two sources of income.…”
Section: Nature-based Tourism As a Diversification Activitymentioning
confidence: 99%
“…Recreation and tourism are important components of multiple national and local economies, contributing to the quality of life, sense of belonging, social connectedness, physical well-being, learning, and other intangible elements (Fossgard and Stensland 2021;Gambarota and Lorda 2017;Prieto Amparán 2020). A significant and growing strand of interest within recreation is nature-based tourism (NbT), which involves an appreciation of the natural environment or traditional cultures dominant in natural areas (Kabil et al 2023;Stemmer et al 2022; World Tourism Organization (UNWTO) 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The data collected using surveys were processed and analysed in more detail using a whole range of quantitative methods of statistical analysis, and IBM SPSS software was used for this purpose most often (Tangeland and Aas, 2011;Fredman et al, 2012;Lee and Jan, 2015;Pinkus et al, 2016;2016;McCreary et al, 2019;Bhuiyan et al, 2021;Fossgard and Stensland, 2021;Marasinghe et al, 2021;Cheng et al, 2022;Gu et al, 2022). Regarding quantitative methods, the most common are multivariate analysis methods, regression analysis (Scott et al, 2007;Mehmetoglu and Normann, 2013;Tangeland et al, 2013;Chubchuwong et al, 2015;Han et al, 2016;Margaryan and Fredman, 2016;Zhang and Chan, 2016;McCreary et al, 2019;Zhang et al, 2020;Bhuiyan et al, 2021), factor (exploratory and confirmatory) analysis (Tangeland and Aas, 2011;Tyrvainen et al, 2014;Lee and Jan, 2015;Han et al, 2016;Pinkus et al, 2016;Zhang et al, 2020;Fossgard and Stensland, 2021;Räikkönen et al, 2021;Cheng et al, 2022), and also cluster analysis, correlation analysis, Chi-square test, t-test and ANOVA (Tangeland and Aas, 2011;De Urioste-Stone et al, 2016;Han et al, 2016;Margaryan and Fredman, 2016;2016;Zhang et al, 2020;Bhuiyan et al, 2021;Fossgar...…”
Section: Pregled Metoda Istraživanja Turizma Temeljenog Na Prirodimentioning
confidence: 99%